Effect of progestogen for women with threatened miscarriage: a systematic review and meta‐analysis. (20th May 2020) - Li, L; Zhang, Y; Tan, H; Bai, Y; Fang, F; Faramand, A; Chong, W; Hai, Y
Abstract : Background: Threatened miscarriage is a common complication of pregnancy. Results of randomised controlled trials on the efficacy of progestogen in the treatment of threatened miscarriage remain inconsistent. Objective: To investigate whether the use of progestogen is associated with improved event rate of live birth and other benefits in women with threatened miscarriage. Search strategy: Ovid MEDLINE, Ovid Embase and Cochrane CENTRAL Register of Controlled Trials from their inception until 8 July 2019. Selection criteria: Randomised controlled trials comparing progestogen with a placebo or no treatment for pregnancy outcomes in women with threatened miscarriage. Data collection and analysis: Two authors independently conducted data extraction and assessed study quality. We calculated risk ratios (RR) and 95% confidence intervals using the Mantel–Haenszel approach for dichotomous outcomes. Main results: Ten trials with a total of 5056 participants were eligible for analysis. The use of progesterone increased the incidence of live birth (RR 1.07, 95% CI 1.00–1.15; P  = 0.04; I 2  = 18%), with benefit only seen with the use of oral progestogen (RR 1.17, 95% CI 1.04–1.31; P  = 0.008; I 2  = 0%) and not with vaginal progesterone (RR 1.04, 95% CI 1.00–1.08; P  = 0.07; I 2  = 0%). Similarly, progestogen reduced the risk of miscarriage (RR 0.73, 95% CI 0.59–0.92), with benefit only seen with oral progestogen and not with vaginal progesterone. Conclusion: Progestogens may have benefits on live birth rate and miscarriage rate for women with threatened miscarriage. These benefits appear to be confined to the use of oral progestogen, and no statistically significant improvements were seen with vaginal progesterone. Tweetable abstract: A meta‐analysis of 10 trials found that progestogens increased live birth rates and reduced miscarriage rates for women with threatened miscarriage. Tweetable abstract: A meta‐analysis of 10 trials found that progestogens increased live birth rates and reduced miscarriage rates for women with threatened miscarriage.